Exogenous shocks and propagation mechanisms in the Ecuadorian economy - Granda Aguilar, Jorge (2023)
This study attempts to document the role and behavior of the real exchange rate in Ecuador. Because of the eclipse of raw materials and particularly of oil, recessive episodes emerge that persist over time, largely due to the excessive procyclical exposure of the economy that significantly appreciated it. The deterioration of the level of activity since the second quarter of 2015, indeed, due to its great intensity, goes beyond the ephemeral oases such as those of 2017 and 2018, recurring again and again without that the therapy applied sequentially ─deficit, external indebtedness and contraction of spending and public investment─ allows to curb the economic decline simultaneously marked by the revaluation of the dollar.